An Advanced MPPT Based on Artificial Bee Colony Algorithm for MPPT Photovoltaic System under Partial Shading Condition - Salmi Hassan; Badri Abdelmajid; Zegrari Mourad; Sahel Aicha; Baghdad Abdenaceur (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Maximum power point tracking (MPPT) algorithms are employed in photovoltaic (PV) systems to make full utilization of PV array output power, which have a complex relationship between ambient temperature and solar irradiation. The power-voltage characteristic of PV array operating under partial shading conditions (PSC) exhibits multiple local maximum power points (LMPP). In this paper, an advanced algorithm has been presented to track the global maximum power point (GMPP) of PV. Compared with the Perturb and Observe (P&O) techniques, the algorithm proposed the advantages of determining the location of GMPP whether partial shading is present.